Investment Intention Among Students: A Modified TPB with Financial Literacy and Social Media - Luh Gede Anggi Ratna Sari; I Gusti Ayu Agung Pradnya Dewi; Caren Angellina Mimaki (Journal of Business and Economics Research (JBE), 2026)
This study aims to analyze the factors influencing the investment intentions of university students in Bali by modifying the Theory of Planned Behavior (TPB). The research integrates financial literacy and social media influence as additional exogenous variables alongside the core constructs of attitude and subjective norms. An explanatory quantitative approach was employed, with data collected from 100 students across Bali using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results of the hypothesis testing indicate that financial literacy and subjective norms have a significant positive effect on attitude towards investment, while social media influence does not. Furthermore, financial literacy, subjective norms, social media influence, and attitude all directly and positively affect investment intention. Attitude also acts as a significant partial mediator in the relationship between financial literacy and subjective norms on investment intention, but not for social media influence. The model demonstrates good predictive power, with an R-square of 0.586 for attitude and 0.660 for investment intention. The findings imply that fostering investment interest among the younger generation requires a dual approach: strengthening foundational knowledge and positive social reinforcement to cultivate supportive attitudes, while strategically leveraging social media as a direct channel for outreach and engagement. These findings provide practical implications for educational institutions and financial authorities in designing effective financial literacy programs and investment communication strategies for the younger generation.